2011
DOI: 10.1002/er.1710
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of natural and conventional working fluids for use in transcritical Rankine cycle using low-temperature geothermal source

Abstract: SUMMARYTheoretical analyses of natural and conventional working fluids-based transcritical Rankine power cycles driven by low-temperature geothermal sources have been carried out with the methodology of pinch point analysis using computer models. The regenerator has been introduced and analyzed with a modified methodology considering the considerable variation of specific heat with temperature near the critical state. The evaluations of transcritical Rankine cycles have been performed based on equal thermodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…The total specific costs of the ORC then account for 2620 €/kW. The total costs are divided by the share of each component which is assumed to be 35% for the heat exchangers, 10% for the pump, 15% for the piping and 40% for the turbine-generator-unit [77][78][79]. For each component, a specific capacity has to be inserted into Equation (6) as follows.…”
Section: Thermoeconomic Modelingmentioning
confidence: 99%
“…The total specific costs of the ORC then account for 2620 €/kW. The total costs are divided by the share of each component which is assumed to be 35% for the heat exchangers, 10% for the pump, 15% for the piping and 40% for the turbine-generator-unit [77][78][79]. For each component, a specific capacity has to be inserted into Equation (6) as follows.…”
Section: Thermoeconomic Modelingmentioning
confidence: 99%
“…I tot (20) When studying the ORC system, not only thermodynamic performance but also economic performance should be considered. In the investment of the ORC system, the evaporator and the condenser occupy a large proportion.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Also, many investigations on ORC are mainly focused on the choices of the working fluid [7][8][9][10][11][12] and its performance [13][14][15][16][17][18][19][20][21]. Hung et al [13] discussed the irreversible loss of the key parts in ORC and found that the maximum irreversible loss happens in the evaporator.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the advantages of using CO 2 are that it is non-toxic, relatively inert in the temperature range of interest, abundant in nature, and cheap [55][56][57][58].…”
Section: Rankine Cyclementioning
confidence: 99%